Toward Coastal Infrastructure Resiliency: An AI-Enabled Decision Support Framework for Multiscale Comprehension and Stakeholder Empowerment. - Xinyue Ye; Newman, Galen; Wei Zhai; Retchless, David; Das, Subasish; Youngjib Ham; Lei Zou; Xiao Huang; Zhe Zhang (Transactions of the American Philosophical Society, 2025)
The article focuses on developing an AI-enabled decision support framework aimed at enhancing coastal infrastructure resiliency in response to climate-related risks. Coastal regions, which house a significant portion of the U.S. population, face increasing vulnerabilities due to climate change, necessitating a comprehensive approach to resilience that integrates data from physical, cyber, and social infrastructures. The proposed framework utilizes digital twin technology to create a dynamic, interactive model that facilitates real-time data analysis, stakeholder engagement, and scenario testing, ultimately empowering communities to make informed decisions regarding infrastructure planning and disaster response. The research emphasizes the importance of interdisciplinary collaboration and community involvement in addressing the unique challenges faced by coastal areas, with implications that extend beyond these regions to inform resilience strategies globally.